2021
DOI: 10.3389/fmicb.2021.779012
|View full text |Cite
|
Sign up to set email alerts
|

Putative Nucleotide-Based Second Messengers in the Archaeal Model Organisms Haloferax volcanii and Sulfolobus acidocaldarius

Abstract: Research on nucleotide-based second messengers began in 1956 with the discovery of cyclic adenosine monophosphate (3′,5′-cAMP) by Earl Wilbur Sutherland and his co-workers. Since then, a broad variety of different signaling molecules composed of nucleotides has been discovered. These molecules fulfill crucial tasks in the context of intracellular signal transduction. The vast majority of the currently available knowledge about nucleotide-based second messengers originates from model organisms belonging either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 155 publications
0
22
0
Order By: Relevance
“…Contrastingly, little is known about nucleotide secondary messengers in archaea. A recent study identified the presence of several cyclic and linear nucleotide molecules in S. acidocaldarius and H. volcanii , although their biological role remains to be determined (Braun et al 2021). Up to date, the only described role for cA 4 is related to type III CRISPR-Cas immunity and future work shall elucidate alternative functions of cA 4 and other secondary nucleotides in archaea, a very likely scenario given that the role of nucleotide messengers in defense is a conserved feature in the other domains of life.…”
Section: Discussionmentioning
confidence: 99%
“…Contrastingly, little is known about nucleotide secondary messengers in archaea. A recent study identified the presence of several cyclic and linear nucleotide molecules in S. acidocaldarius and H. volcanii , although their biological role remains to be determined (Braun et al 2021). Up to date, the only described role for cA 4 is related to type III CRISPR-Cas immunity and future work shall elucidate alternative functions of cA 4 and other secondary nucleotides in archaea, a very likely scenario given that the role of nucleotide messengers in defense is a conserved feature in the other domains of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one might ask the question why in particular cyclic di-AMP and cyclic di-GMP had been selected to ubiquitously direct biofilm related physiology and metabolism. As an argument from a chemical perspective, in comparison to the monocyclic cyclic AMP and cyclic GMP, the covalent bonds in the di-cyclic molecules experience less tension and thus lead to more stable molecules [113] On the other hand, a wide spectrum of diverse cyclic di-nucleotides including cyclic AMP-GMP, cyclic oligo-nucleotides and even pyrimidine-based cyclic nucleotides have been recently unravelled to occur [114][115][116]. To what extent these and other nucleotide-based signaling molecules play a role in physiology and metabolism of the majority of under-investigated environmental microbes beyond phage defense systems remains to be determined.…”
Section: Figurementioning
confidence: 99%
“…Indeed, OG0001177 and OG0001178 proteins are associated with pilus assembly proteins and/or surface proteins, while OG0001176 and OG0000094 can be associated with cell shape or gene regulation (the latter is not identified in our pipeline but its gene is always located downstream of the OG0001176 gene). Cluster D is related to nucleic acid metabolism or cellular signal transduction (Braun et al 2021), whereas cluster E code for the four proteins that compose the methyl-coenzyme M reductase, which is implied in methane formation (Chen et al 2020). Very recently, two potential clusters for PM biosynthesis were identified using bacterial proteins from PG biosynthesis as BLAST queries (Subedi et al 2021) was not considered for phylogenetic analysis because, compared to the aforementioned proteins, no homologous protein was identified in the representative bacterial database (nor for OG0001215 and OG0000138).…”
Section: Genetic Environment Of Candidate Proteinsmentioning
confidence: 99%